2018
DOI: 10.1016/j.cub.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Space Is Controlled by Apoptosis-Induced Change of Local Epithelial Topology

Abstract: During the initial stage of tumor progression, oncogenic cells spread despite spatial confinement imposed by surrounding normal tissue. This spread of oncogenic cells (winners) is thought to be governed by selective killing of surrounding normal cells (losers) through a phenomenon called "cell competition" (i.e., supercompetition). Although the mechanisms underlying loser elimination are increasingly apparent, it is not clear how winner cells selectively occupy the space made available following loser apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 62 publications
2
59
0
Order By: Relevance
“…How tissues compete with each other for space is of great interest with many open biological questions being pursued in the experimental cell biology literature [5,21,45]. For example, in cancer invasion in an epithelial tissue a key question is whether cancer cells will eventually replace the entire healthy tissue or can the cancer cells coexist with the healthy cells?…”
Section: Mechanical Cell Competitionmentioning
confidence: 99%
“…How tissues compete with each other for space is of great interest with many open biological questions being pursued in the experimental cell biology literature [5,21,45]. For example, in cancer invasion in an epithelial tissue a key question is whether cancer cells will eventually replace the entire healthy tissue or can the cancer cells coexist with the healthy cells?…”
Section: Mechanical Cell Competitionmentioning
confidence: 99%
“…6E ) and the expansion of the Ras V12 cell area which are close to the clone boundaries ( Fig. 6F, Ras V12 cell apical area near clone boundaries increased by 79% on average over 700min in controls, while only 24% for Ras V12 and sSpitz expressing cells), which are the cells that should compensate for most of the area left by the WT dying cells[37]. This suggested that cell elimination through ERK downregulation contributed to pretumoural clone expansion and global replacement of the WT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Vertex models have been widely used in epithelial monolayer modelling including cell sorting [45], germband extension [46], ventral furrow formation [47], cell division and tissue elongation [48], wound healing [49,50], as well as tumor growth [51]. Vertex models have been used in studies of mechanical cell competition [34], as well as to infer the role of local epithelial topology on mutant clone expansion [23]. Vertex models, however, have some key disadvantages, including the difficulty to model arbitrary cell shapes, isolated cells, or cell clusters.…”
Section: Cell-based Modelsmentioning
confidence: 99%